Vai trò của cha mẹ trong việc sử dụng công nghệ của thế hệ Gen Z - Phùng Thái Minh , Trang; Nguyễn Hữu, Thọ; Nguyễn Văn , Hóa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Generation Z (Gen Z) is the core workforce contributing to economic growth. However, research on the role parents play in shaping behaviours among college students - Gen Z - is still limited, both nationally and internationally. Therefore, the study fills the gap in the literature by investigating the effects of parents on Gen Z’s technological attitudes (TRI) and usage. Three methods used in the study are multiple linear regression, ordinal logic regression, and structural equation model. Based on data surveyed from 640 university students in Vietnam from May 2022 to September 2022, the results report that parents' technological knowledge and education have an impact on students' TRI and usage. The results are robust to these methods and when control variables are involved. Our findings have implications for policymakers on the vital role parents play in providing high-quality Gen Z human resources to society in the digital era.
Keywords: Parental influence; Technological knowledge; Technology usage; TRI; Generation Z